Lipoprotein(a) as an early marker of cardiovascular events in high-risk subjects: insights from the Moli-sani cohort study - Francesco Gianfagna; Simone Poli; Simona Costanzo; Simona Costanzo; Augusto Di Castelnuovo; Teresa Panzera; Amalia De Curtis; Sara Magnacca; Mariarosaria Persichillo; Lorenzo De Santi; Claudia Cristofani; Daniele Loffredo; et al. (Frontiers in Cardiovascular Medicine)
Background and aimsEpidemiological studies have revealed the role of lipoprotein(a) [Lp(a)] in the etiopathogenesis of cardiovascular disease (CVD). We analyzed the association between Lp(a) and the risk of a major cardiovascular event in subjects with previous CVD.MethodsThe analysis was conducted on the Moli-sani study population (24,325 individuals aged ≥35 years, recruitment from 2005 to 2010), focusing on subjects with prior CVD. Data from standardized questionnaires and blood pressure, anthropometric, and lab measurements were collected. Lp(a) levels were measured using biobanked samples. The cohort was followed for cardiovascular events. The association between Lp(a) levels and risk of major adverse cardiovascular events was analyzed using Kaplan–Meier and Cox regression models.ResultsIn total, 1,284 subjects reported a history of CVD at baseline. The mean ± SD Lp(a) level was 23.3 ± 26.0 mg/dl and 51 subjects (4.0%) had levels ≥90 mg/dl. After a median of 7.3 years, 307 CVD events were recorded and validated. Subjects belonging to the highest Lp(a) level group (≥90 mg/dl) showed a worse trend during early follow-up compared with the lowest level group (<30 mg/dl), with a peak during the first 18 months [hazard ratio (HR) = 3.43, 95% confidence interval (CI): 1.43–8.27]. This increase was higher in subjects with dyslipidemia not treated with statins and those with multiple previous CVD events (HR = 11.0, 95% CI: 1.98–61.1; HR = 25.6, 95% CI: 7.83–83.8).ConclusionsHigh Lp(a) levels were associated with an increased risk of early secondary cardiovascular events in individuals with a history of multiple CVDs or non-treated dyslipidemia, suggesting that lipoprotein(a) is a modifiable biomarker that can be measured at different times for CVD risk assessment.